Anatomy & physiology : (McGraw-Hill, 2007)
Gunstream is manual presents the fundamentals of human anatomy and physiology in an easy-to-read manner appropriate for allied health students. Designed especially for a one-semester course, the Essentials Version features a concise writing style, 37 self-directing exercises, full-color photomicrographs in the Histology Atlas, and numerous illustrations in each exercise..